2020
DOI: 10.3389/fpsyg.2020.00789
|View full text |Cite|
|
Sign up to set email alerts
|

Training Positive Rumination in Expressive Writing to Enhance Psychological Adjustment and Working Memory Updating for Maladaptive Ruminators

Abstract: Rumination is associated with psychological adjustment and working memory (WM) capacity. Studies have shown that psychological interventions can reduce negative rumination and improve psychological adjustment and WM capacity. The present study investigated the effect of positive rumination training in expressive writing on psychological adjustment and WM updating capacity. Within an experimental design, positive rumination was manipulated for 10 participants who were maladaptive ruminators in an experiment usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…The present study indicated that EW interventions helped high test-anxious individuals with high working memory capacity to alleviate state anxiety and CUP effect. Previous research has shown that participants who use more cognitive words during writing significantly increase their working memory capacity [25,26] and minimize intrusive and avoidant thoughts about bad occurrences [21,22,33]. The present study supports these ideas and shows that the high test-anxious participants who used more emotional and cognitive words in the written content were less affected by test stress.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present study indicated that EW interventions helped high test-anxious individuals with high working memory capacity to alleviate state anxiety and CUP effect. Previous research has shown that participants who use more cognitive words during writing significantly increase their working memory capacity [25,26] and minimize intrusive and avoidant thoughts about bad occurrences [21,22,33]. The present study supports these ideas and shows that the high test-anxious participants who used more emotional and cognitive words in the written content were less affected by test stress.…”
Section: Discussionsupporting
confidence: 86%
“…EW interventions have emotionally cathartic and cognitive adjustment functions, which could help test-anxious individuals reduce task-irrelevant thinking [23]. Studies have shown that writing down feelings and thoughts about forthcoming exams can aid students in reducing depression and anxiety [24], enhance working memory capacity [25,26], and improve test performance [27]. High test-anxious individuals can write to vent negative emotional experiences about exams, reduce stressful experiences, and relieve the load on their cognitive system.…”
Section: Introductionmentioning
confidence: 99%
“…Positive emotion expressive writing has been shown to alleviate intrusive rumination to facilitate personal growth (Glass et al, 2019). However, expressions of both positive and negative emotions tend to reduce maladaptive ruminations and increase positive rumination and psychological adjustment (Yang & Li, 2020). Therefore, it is possible that both positive and negative emotional expressivity may mediate the relationship between intrusive rumination and PTG.…”
Section: Introductionmentioning
confidence: 99%
“…Tey learn to take the initiative to self-regulate, gradually change negative thoughts, and establish positive coping styles. Together, these skills help patients cope with their disease, deal with shame, and improve their confdence to overcome stigma [33].…”
Section: Discussionmentioning
confidence: 99%